Regulation of gene expression in milk secretory pathways during secretory activation in Holstein cows - E.M. Shangraw; T.B. McFadden (Journal of Dairy Science)
ABSTRACT: Increased transcription of genes involved in lactose synthesis is a key feature of secretory activation of the mammary gland. We determined which genes are transcriptionally regulated during the transition from colostrum to milk in cows and whether more frequent milking of one udder half would increase milk yields and alter gene expression. We enrolled 12 Holstein cows immediately after calving, harvested colostrum, then randomly assigned one udder half to 12-h (2X) or 6-h (4X) milking intervals for 48 h after first milking. After 48 h, all quarters were milked twice daily until d 7, when final quarter milk yields were collected. Yields and composition of colostrum and milk were recorded for each 12-h interval. After each milking, a strip sample of hind milk was collected for isolation of RNA from milk fat and quantification of selected transcripts via quantitative PCR. Milk, milk fat, total protein, and lactose yields increased significantly over the initial 48 h and at d7 after calving. Quarters on 4X treatment produced more milk than the contralateral 2X quarters. Genes upregulated concomitantly with milk yields encoded α-LA (LALBA), β-1,4-galactosyltransferase (B4GALT1), fatty acid synthase (FASN), β-CN (CSN2), and folate receptor α (FOLR1). Downregulated genes encoded monosaccharide transporters (SLC2A3, SLC2A8, SLC35A2) and enzymes involved in galactose synthesis (HK1, PGM1, GALE). Three genes were initially downregulated but later upregulated at d7 (LPIN1, SLC2A1, UGP2). Notably, milking frequency had no effect on gene expression. Sequential upregulation first of genes encoding the former enzymes, then of UGP2, may be necessary for copious milk production. However, the local effects of milking frequency on milk production during lactogenesis do not appear to be controlled by transcription of these genes related to lactose synthesis.